An updated prostate cancer staging nomogram (Partin tables) based on cases from 2006 to 2011. (26th July 2012) - Eifler, John B.; Feng, Zhaoyang; Lin, Brian M.; Partin, Michael T.; Humphreys, Elizabeth B.; Han, Misop; Epstein, Jonathan I.; Walsh, Patrick C.; Trock, Bruce J.; Partin, Alan W.
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? Pathological stage after radical prostatectomy can be accurately predicted by serum prostate‐specific antigen level, clinical stage and biopsy Gleason sum, the 'Partin tables'. Since the previous publication of the Partin tables, an updated Gleason scoring system has been established and incremental changes have occurred in the clinical characteristics of patients diagnosed with prostate cancer. The current analysis updates the Partin nomogram in a contemporary cohort of patients. Objective To update the 2007 Partin tables in a contemporary patient population. Patients and Methods The study population consisted of 5, 629 consecutive men who underwent RP and staging lymphadenectomy at the Johns Hopkins Hospital between January 1, 2006 and July 30, 2011 and met inclusion criteria. Polychotomous logistic regression analysis was used to predict the probability of each pathologic stage category: organ‐confined disease (OC), extraprostatic extension (EPE), seminal vesicle involvement (SV+), or lymph node involvement (LN+) based on preoperative criteria. Preoperative variables included biopsy Gleason score (6, 3+4, 4+3, 8, and 9–10), serum PSA (0–2.5, 2.6–4.0, 4.1–6.0, 6.1–10.0, greater than 10.0 ng/mL), and clinical stage (T1c, T2c, and T2b/T2c). Bootstrap re‐sampling with 1000 replications was performed to estimate 95% confidence intervals for predicted probabilities of each pathologic state. Results The median PSA was 4.9 ng/mL, 63% had Gleason 6 disease, and 78% of men had T1c disease. 73% of patients had OC disease, 23% had EPE, 3% had SV+ but not LN+, and 1% had LN+ disease. Compared to the previous Partin nomogram, there was no change in the distribution of pathologic state. The risk of LN+ disease was significantly higher for tumours with biopsy Gleason 9–10 than Gleason 8 (O.R. 3.2, 95% CI 1.3–7.6). The c‐indexes for EPE vs. OC, SV+ vs. OC, and LN+ vs. OC were 0.702, 0.853, and 0.917, respectively. Men with biopsy Gleason 4+3 and Gleason 8 had similar predicted probabilities for all pathologic stages. Most men presenting with Gleason 6 disease or Gleason 3+4 disease have <2% risk of harboring LN+ disease and may have lymphadenectomy omitted at RP. Conclusions The distribution of pathologic stages did not change at our institution between 2000–2005 and 2006–2011. The updated Partin nomogram takes into account the updated Gleason scoring system and may be more accurate for contemporary patients diagnosed with prostate cancer.